Assessing landscape fragmentation and its driving factors in arid regions: A case study of the Manas River, China - Jiaji Li; Jinxuan Wang; Yazhen Du; Xinyue Hou; Ruru Xi; Yuxuan Yang (Ecological Indicators, 2025)
Climate change and frequent socioeconomic activities in the Manas River have exacerbated land use transformation and watershed landscape pattern fragmentation, causing a sharp decline in natural wetlands and degrading ecological functions in critical ecological zones. However, previous studies on landscape fragmentation in arid regions have often lacked analysis of long-term trends and driving factors, and comprehensive long-term research on the mechanisms and dynamics of landscape fragmentation in the Manas River Watershed is limited. In this study, the trends and driving factors of landscape fragmentation in the Manas River Watershed from 1980 to 2020 were investigated by using land use raster data, landscape pattern indices, principal component analyses, and grey correlation analyses. The findings indicate that 1) farmland and construction land in the Manas River Watershed surged over 40 years, contrasting with sharp declines in grasslands, woodlands, glaciers and water bodies. Unused land remained stable. 2) Large-scale land use transitions occurred primarily after 1995. The main land use conversions were from grasslands, woodlands, and unused land to farmland and construction land; moreover, melting converted glaciers into unused land. 3) From 1980 to 2020, the landscape of the Manas River Watershed fragmented, which intensified over time, with patches dispersing and complexifying. 4) Manas landscape fragmentation stems from climate change and human activities. Human factors, notably town GDP, road length, and farmland area, are the key drivers, outweighing natural climate impacts. The finding offers insights into an enhanced understanding of landscape fragmentation in arid regions. This research can serve as a valuable reference for work concerning ecological environmental management and territorial spatial planning for the Manas River Watershed.